Study of Potential Application Air Curtains in Livestock Premises at Cattle Management Farms - Aleksey Kuzmichev; Aleksei Khimenko; Dmitry Tikhomirov; Dmitry Budnikov; Marek Jasiński; Vadim Bolshev; Ivan Ignatkin (Agriculture, 2023)
Recommendations on the selection of air curtains and the calculation of their parameters for livestock premises in cattle management farms are made. The air curtain functioning principle is analyzed from the air jet theory point of view. The block diagram and modular design of air curtains with a variable air jet direction vector and with controlled slit width are designed. Laboratory tests of the newly designed air curtain structure are performed in accordance with the microclimate requirements for the cattle management farm premises. Based on the experimental results, the major air curtain parameters are calculated for the range from 10° to 60° of angle α between the direction of the air jet outward from the air curtain slit and aperture plane, and for the air curtain slit width b0 in the range from 0.05 m to 0.15 m with the account of the wind speed Vw variations. Calculated values for amounts of energy that have to be consumed to ensure the required air jet velocity, in the output from the air curtain, and those for the quantity of thermal energy required to heat the air supplied to the air curtain, depending on the angle α and on the slit width b0, can be helpful for selecting the power capacity of both the air curtain fan and electric heater. A block diagram of the air curtain control for cattle management farm premises is designed, enabling automatic control of the airflow rate, the angle of the air jet output from the air curtain slit, and the temperature of the heated air supplied to the air curtain, considering particular climate conditions. According to the preliminary estimate, applications of the newly designed air curtain will make it possible to reduce the energy consumed to maintain the required microclimate conditions in cattle management premises by 10% to 15% in the cold period.